Solution of Beam Structure Analysis Using SAP2000 (International Journal of Innovative Research in Computer Science & Technology, 2023)
The beam structure is an essential  structural element for construction professionals, and most  engineers should be familiar with beams. The type of beam  structure discussed in this paper is a simple beam structure.  Calculating the forces and structural deformations  numerically takes longer and require good accuracy. In this  increasingly sophisticated era, various kinds of software are  available, one of which is SAP2000, which can be used to  obtain internal forces and structural deformations quickly  and accurately. In this paper, a simple beam structure is  modeled and analyzed using SAP2000 software. This paper  aims to provide solutions for analyzing structures,  especially simple beams. Manual calculations will also  validate this paper according to the requirements of static  balance. Furthermore, the analysis results using SAP2000  software and manual calculations have been obtained and  validated. The analysis results showed that the values  obtained did not significantly differ. So it can be concluded  that structural analysis with SAP2000 software can be a fast  and accurate solution.
Keywords: beam structural; simple beam; SAP2000